2015
DOI: 10.4238/2015.april.22.6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of soluble receptor for advanced glycation end-products in aortic valve calcification patients

Abstract: ABSTRACT. The soluble receptor for advanced glycation endproducts (sRAGE) shows a close relationship with atherosclerosis. The goal of this study was to compare the levels of sRAGE in patients with and without aortic valve calcification and to investigate the relationship between them. After transthoracic echocardiographic examination, 120 male patients with aortic valve calcification and 120 age-matched male controls without aortic valve calcification were included in our study. sRAGE levels were compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…For example, serum sRAGE levels are inde-pendently correlated with a marker of central aortic stiffness, therefore suggesting a potential role for RAGE in this process (260,335). Other researchers have found that sRAGE is a predictor of aortic valve calcification (346) and correlates with dysfunctional aortic microstructure (33). It is also an inverse marker of left ventricular hypertrophy in patients with chronic kidney disease, therefore indicating that the RAGE pathway may be a causal risk factor for cardiac hypertrophy in this instance (174).…”
Section: H156mentioning
confidence: 99%
“…For example, serum sRAGE levels are inde-pendently correlated with a marker of central aortic stiffness, therefore suggesting a potential role for RAGE in this process (260,335). Other researchers have found that sRAGE is a predictor of aortic valve calcification (346) and correlates with dysfunctional aortic microstructure (33). It is also an inverse marker of left ventricular hypertrophy in patients with chronic kidney disease, therefore indicating that the RAGE pathway may be a causal risk factor for cardiac hypertrophy in this instance (174).…”
Section: H156mentioning
confidence: 99%